Gas–liquid mass transfer in the presence of ionic surfactant: effect of counter‐ions and interfacial turbulence. (21st February 2013) - Zhang, Shuo; Wang, Dong; Bu, Fang; Zhang, Xingwen; Fan, Pingping
<x xml:space="preserve">Abstract</x> This work investigated the effect of counter‐ions and interfacial turbulence on oxygen transfer from gas to liquid phase containing ionic surfactant, and experiments were performed in a mechanically stirred reactor with flat gas–liquid interface. Counter‐ions in terms of hydration ability and polarizability influence the interfacial coverage of ionic surfactants (i.e. cetytrimethylammonium bromide (CTAB) and cetytrimethylammonium chloride) with the same hydrocarbon chain length, producing hindrance but in different extent on oxygen transfer. The addition of electrolyte (NH4Br) substantially reduced the interfacial tension and surface charge of micelles (zeta potential) in CTAB system, and this salt effect greatly compressed interfacial double layer leading to gas transfer inhibition. The surface charge, aggregation number as well as stability of micelles formed above the critical micelle concentration could also alter interfacial configuration of surfactant layer reflected by gas absorption rate. Liquid turbulence was analyzed to decide the role of surfactant present in water on gas–liquid mass transfer, since Marangoni instability effect playing positive role should be taken into consideration under moderate liquid flow, while in turbulent system, contribution of Marangoni effect became overshadowed and consequently surfactant pose 'barrier' effect on gas transfer due to its surface active nature. Copyright © 2013 John Wiley & Sons, Ltd.